Atypical Intraductal Cribriform Proliferations of the Prostate Exhibit Similar Molecular and Clinicopathologic Characteristics as Intraductal Carcinoma of the Prostate. (April 2017) - Hickman, Richard A.; Yu, Hui; Li, Jianhong; Kong, Max; Shah, Rajal B.; Zhou, Ming; Melamed, Jonathan; Deng, Fang-Ming
Abstract : Atypical intraductal cribriform proliferations of the prostate (AIP) are loose cribriform proliferations of luminal cells that exhibit greater architectural complexity and/or nuclear atypia than high-grade prostatic intraepithelial neoplasia (HGPIN), but lack the diagnostic criteria for intraductal carcinoma (IDC). The significance of AIP has not been formally established. We compared the clinical, morphologic, and immunohistochemical characteristics of AIP with classic IDC in 310 radical prostatectomy specimens that were received over an 18-month period. Of the 310 cases, 46 cases had AIP only (n=10), IDC only (n=6), or AIP coexisting with IDC (n=30). The ERG status of all 46 AIP/IDC cases was identical to the nearby acinar carcinoma, contrasted to just 3 cases of HGPIN (7%, P <0.01). The degree of uniform phosphatase and tensin homolog (PTEN) loss in 34 selected cases was identical in AIP and IDC (66.7%). No foci of HGPIN showed uniform PTEN loss; there was only 38% concordance of PTEN expression pattern between HGPIN and the nearby acinar carcinoma, unlike AIP and IDC (77% and 81%, respectively, P <0.01). AIP-associated and/or IDC-associated carcinoma (n=46) showed a higher stage and grade compared with acinar-only carcinoma (n=264, P <0.01). AIP-associated carcinoma had similar clinicopathologic features as IDC-associated carcinoma, including preoperative prostate-specific antigen, Gleason score, extraprostatic extension, seminal vesicle invasion, and lymph node metastasis (n=36, P >0.05). In conclusion, AIP shares similar ERG/PTEN immunoprofiles and exhibits similar clinical behavior as IDC, warranting immediate repeat biopsy when AIP is identified on biopsy, as is recommended in the most recent WHO Classification of Tumours of the Urinary System and Male Genital Organs, 2016.